## Solving the Equation (x+12)^2 = 9

This equation involves a squared term, so we'll need to use the square root property to solve for *x*. Here's how to break down the solution:

### 1. Isolate the Squared Term

The squared term is already isolated on the left side of the equation.

### 2. Take the Square Root of Both Sides

To undo the squaring, take the square root of both sides of the equation. Remember that taking the square root results in both a positive and a negative solution.

```
√((x+12)^2) = ±√9
```

### 3. Simplify

Simplify the square roots:

```
x + 12 = ±3
```

### 4. Solve for x

Now we have two separate equations to solve:

**Case 1:**x + 12 = 3**Case 2:**x + 12 = -3

**Case 1:**
Subtract 12 from both sides to get:
x = -9

**Case 2:**
Subtract 12 from both sides to get:
x = -15

### 5. Solutions

Therefore, the solutions to the equation (x+12)^2 = 9 are **x = -9** and **x = -15**.